If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6h-6+2h=8h-6
We move all terms to the left:
6h-6+2h-(8h-6)=0
We add all the numbers together, and all the variables
8h-(8h-6)-6=0
We get rid of parentheses
8h-8h+6-6=0
We add all the numbers together, and all the variables
=0
h=0/1
h=0
| 8(2+v)+33v=13v | | 25*7=x | | x−3−2(6−2x)=2(2x−5 | | r/3+-9=-7 | | 75+25(7)=x | | (p-6)/(3)=-15 | | 3*(3y-5)=32 | | 4+-7x=74 | | t-28*5=8 | | x×3=2 | | (f+4)/(2)=5 | | 8=h-67-4 | | 2=c/5-3 | | 13-2h=9 | | r/2-10=-7 | | 520-99=x | | g/3+7=9 | | f(10)=520-11(9) | | 7x-x=56 | | -5+3f=1 | | -2d+-4=-8 | | 5u=u+(^ | | 9*8=n*3 | | 14*3=6*n | | 58x+2182x-27=56(40x+33) | | 14*6=n*3 | | 48*n=48 | | 10r-6r+7=9r+7-r | | z2-16=0 | | 2x+2=5x+1-3x+1 | | 28=7-3w | | v/2+3=12 |